Chuetas of Majorca: The case of the Tarongi Brothers - Picazo Muntaner, Antoni (Cuadernos Judaicos, 2020)
In 1677 the Inquisition captured more than two hundred people from Palma de Mallorca who were Judaizing. This group was called chueta. This caused a series of consequences that would be much more damaging some years later, in 1691. Certainly, the action of the Holy Office precipitated a greater secrecy among the Judaizers, but also a desire to flee to the land of liberties, generally Livorno, or the rupture of family solidarity. A special case was that of the Tarongi family, and that of their two brothers, the intellectual guides of that community.